Role of HDACs in normal and malignant hematopoiesis - Wang, Pan; Wang, Zi; Liu, Jing (Molecular cancer, 2020)
Normal hematopoiesis requires the accurate orchestration of lineage-specific patterns of gene expression at each stage of development, and epigenetic regulators play a vital role. Disordered epigenetic regulation has emerged as a key mechanism contributing to hematological malignancies. Histone deacetylases (HDACs) are a series of key transcriptional cofactors that regulate gene expression by deacetylation of lysine residues on histone and nonhistone proteins. In normal hematopoiesis, HDACs are widely involved in the development of various lineages. Their functions involve stemness maintenance, lineage commitment determination, cell differentiation and proliferation, etc. Deregulation of HDACs by abnormal expression or activity and oncogenic HDAC-containing transcriptional complexes are involved in hematological malignancies. Currently, HDAC family members are attractive targets for drug design, and a variety of HDAC-based combination strategies have been developed for the treatment of hematological malignancies. Drug resistance and limited therapeutic efficacy are key issues that hinder the clinical applications of HDAC inhibitors (HDACis). In this review, we summarize the current knowledge of how HDACs and HDAC-containing complexes function in normal hematopoiesis and highlight the etiology of HDACs in hematological malignancies. Moreover, the implication and drug resistance of HDACis are also discussed. This review presents an overview of the physiology and pathology of HDACs in the blood system.